A new method of fault estimation and tolerant control for fuzzy systems against time-varying delay. (November 2020) - Sun, Shaoxin; Wang, Yingchun; Zhang, Huaguang; Xie, Xiangpeng
Abstract: In the study, the issues of observer-based fault estimation (FE) as well as active fault-tolerant control (FTC) are considered based on a series of Takagi–Sugeno (T–S) fuzzy models against time-varying delay. Utilizing these obtained ( k − 1 )th messages, a new k -step T–S fuzzy fast adaptive FE method is suggested to construct this observer. And a full-order controller is suggested to make the closed-loop system stable by compensating this fault effect. In contrast to the existing study works, the addressed controller can be carried out in a wider application scope. A fuzzy Lyapunov–Krasovskii functional method is utilized to analyze the stability of the closed-loop system. Meanwhile, sufficient stability conditions are proposed through linear matrix inequalities (LMIs) calculated by Matlab toolbox. Finally, the merits of this suggested approach are demonstrated via two simulation examples.